SPE International Symposium on Oilfield Chemistry 2005
DOI: 10.2118/93005-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of the Water Formation Salinity in the Performance of Gels for Water Shutoff

Abstract: In this work a gel of an acrylamide based polymer crosslinked with organic reagents was studied. This gelling system was one of the commonly used in water conformance treatments. Once formed in bottle tests the gel was placed in contact in several proportions with water of various salinities. The tests where carried out at 266°F, and the changes were registered as a function of time. It was found that the gel swelled until a constant final volume. This value depende the difference between the salinity of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Anyway, the experimental results presented above prove that gellan gum provides sufficiently high-pressure gradients (around 50 psi/ft = 1 MPa/m = 0.2 MPa/0.2 m) in 1 mm-width fractures during the post-flush with high salinity brine (150 g/L) (Figure 12). This is a remarkable result because post-flush brine salinity greatly influences the stability of HPAM gels in fractures [63]. For example, the authors of [64] found out that HPAM + Cr +3 gel failed at 0.45 MPa/m (20 psi/ft) during the post-flush with 8% salinity brine; as a consequence, there was no redirection of fluids accomplished.…”
Section: Plugging Behavior Of Gellan Gum In Laboratory Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anyway, the experimental results presented above prove that gellan gum provides sufficiently high-pressure gradients (around 50 psi/ft = 1 MPa/m = 0.2 MPa/0.2 m) in 1 mm-width fractures during the post-flush with high salinity brine (150 g/L) (Figure 12). This is a remarkable result because post-flush brine salinity greatly influences the stability of HPAM gels in fractures [63]. For example, the authors of [64] found out that HPAM + Cr +3 gel failed at 0.45 MPa/m (20 psi/ft) during the post-flush with 8% salinity brine; as a consequence, there was no redirection of fluids accomplished.…”
Section: Plugging Behavior Of Gellan Gum In Laboratory Experimentsmentioning
confidence: 99%
“…Based on the information presented above, when there is an ample supply of fresh water and the budget is not restricted to 4 USD/kg of dry powder, gellan gum may prove to be a preferable alternative to HPAM. Furthermore, the samples of gellan gum gels obtained during the Kumkol pilot test (2013) were aged for 5 years without any evidence of gel degradation [63]. In reservoir conditions, microbial degradation of biopolymers may also be prevented through the appropriate use of biocides [80].…”
Section: Primary Disadvantages Of Hpammentioning
confidence: 99%
“…There is a breakthrough of water injected for pressure maintenance or enhanced oil recovery. Llamedo et al (2005) explained the effect of salinity of formation water on performance of a gel system for water shut-off. Residual resistance factor (RRF) was lower when the water used for preparation of gel and formation water had similar salinity.…”
mentioning
confidence: 99%